Effects of Different Land Use Types on Surface Temperature in the Northwest Arid Zone - Yang, Liangyan; Shi, Lei (International Journal of Natural Resources and Environmental Studies, 2024)
This study analyzed the spatial and temporal characteristics of surface temperature in Uttarakhand Banner, and explored the correlation between land use types and surface temperature. The results show that the surface temperature of Urumqi Banner is greatly influenced by the change of land use types, and the difference of surface temperature between different land use types is obvious; the spatial and temporal trend of surface temperature in Urumqi Banner is different from the trend of gradual warming of the global climate change, which is mainly due to the change of the land use types by human activities.